2012
DOI: 10.1175/jtech-d-11-00128.1
|View full text |Cite
|
Sign up to set email alerts
|

Observing Ocean Surface Waves with GPS-Tracked Buoys

Abstract: Surface-following buoys are widely used to collect routine ocean wave measurements. While accelerometer and tilt sensors have been used for decades to measure the wave-induced buoy displacements, alternative global positioning system (GPS) sensor packages have been introduced recently that are generally smaller, less expensive, and do not require calibration. In this study, the capabilities of several GPS sensors are evaluated with field observations in wind-sea and swell conditions off the California coast. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
109
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(111 citation statements)
references
References 14 publications
2
109
0
Order By: Relevance
“…Following the Herbers et al (2012) method, horizontal velocities are converted to sea surface elevation statistics using linear theory:…”
Section: A Surface Waves and Wave Breakingmentioning
confidence: 99%
“…Following the Herbers et al (2012) method, horizontal velocities are converted to sea surface elevation statistics using linear theory:…”
Section: A Surface Waves and Wave Breakingmentioning
confidence: 99%
“…Horizontal velocity spectra were found using the Welch method, where the time series is split into 256 second windows with 75% overlap; a Hamming taper was applied to each window, and then the windows were averaged together, giving each 10-minute spectrum approximately 28 degrees of freedom. Wave energy spectra were estimated using linear theory, which relates horizontal wave orbital velocities to surface elevation, a method developed by Herbers et al (2012): (6) where E ( f ) is the wave energy spectrum in m 2 Hz −1 , E UU ( f ) and E VV ( f ) are the horizontal velocity spectra, and f is intrinsic wave frequency.…”
Section: Wave Spectramentioning
confidence: 99%
“…As described in Herbers et al (2012), the directional moments are found from, (7) where Q xz and Q yz are the quadrature-spectra of horizontal and vertical displacements. The wave direction and directional spread are then found from the directional moments, (8) and (9) Turbulence Turbulent dissipation rates in the upper half meter of the ocean were estimated using the second order structure function of velocities recorded from a Nortek 2 MHz Aquadopp HR mounted underneath the SWIFT drifters (Thomson, 2012).…”
Section: Wave Spectramentioning
confidence: 99%
“…The motion of the platform is measured using a GPS receiver (Microstrain 3DM-GX3-35) at 4 Hz, with a horizontal velocity precision of 0.05 m/s. Horizontal velocity vectors are decomposed into mean and wave orbital velocity components that are used to infer wave energy spectra (Herbers et al, 2012). The natural frequency of the buoy, with a period of 1.3 seconds, is damped by a small heave plate Elementa: Science of the Anthropocene • 4: 000097 • doi: 10.12952/journal.elementa.000097 to allow observations of wave motions from low frequency swells to high frequency wind waves.…”
Section: Data Collectionmentioning
confidence: 99%